Influence of caffeine and sodium citrate ingestion on 1,500-m exercise performance in elite wheelchair athletes: A pilot study - Flueck, J. L.; Mettler, S.; Perret, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The aim of this study was to investigate whether caffeine and/or sodium citrate have an ergogenic effect on the 1,500-m exercise performance in elite wheelchair athletes. A placebo-controlled, randomized, cross-over and double-blind study design was conducted with the four treatments placebo, caffeine, sodium citrate and the combination of caffeine and sodium citrate. Nine healthy, elite wheelchair-racing athletes (median: [min; max] age: 28 y [23; 54]; height: 173 cm [165; 188]; weight: 62.9 kg [48.9; 68.4], category T53/54) completed the study. All athletes were national team members, including several Paralympic Games, World and European Championship medalists. The athletes performed a 1,500-m time trial four times on a wheelchair training roller. Time to complete 1,500-m, pH, bicarbonate and sodium concentration as well as lactate concentration were measured. The time to complete 1,500-m was not significantly different between the four treatments (placebo: 170.6 s [141.7; 232.0]; caffeine: 179.5 s [134.8; 239.6]; sodium citrate: 178.3 s [136.4; 247.1]; com- bination: 177.6 s [136.1; 256.2]). However, pH and bicarbonate concentrations were significantly increased with sodium citrate ingestion compared with placebo. Moreover, maximal lactate concentrations were sig- nificantly higher in the caffeine and the combination treatment compared with placebo. The supplementation with sodium citrate and/or caffeine did not provide an ergogenic effect on the 1,500-m exercise performance in wheelchair elite athletes.